2020
DOI: 10.1177/1356336x20976687
|View full text |Cite
|
Sign up to set email alerts
|

Principals’ involvement in comprehensive school physical activity programmes: A social-ecological perspective

Abstract: To support school physical education, United States (US) national organizations in medicine, health, and education recommend that schools adopt comprehensive school physical activity programmes (CSPAPs). An important factor in successful CSPAP implementation is the involvement of the school principal. The purpose of this study was to examine relationships between principals’ self-reported CSPAP involvement and their social-ecological-based perceptions about CSPAPs. We analysed survey responses from a national … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 48 publications
0
12
0
1
Order By: Relevance
“…School managers were often said to be busy and did not welcome programmes that clashed with their plans. Orendorff et al (2020) found that, although school principals might agree on the benefits of a physical health programme for students, they expressed less agreement about their personal involvement in the programme, as some felt doing so was beyond their call of duty. In Poland, Woynarowska-Soldan (2015) found that school leaders had limited involvement in establishing and managing health-promotion initiatives among school staff.…”
Section: Resultsmentioning
confidence: 99%
“…School managers were often said to be busy and did not welcome programmes that clashed with their plans. Orendorff et al (2020) found that, although school principals might agree on the benefits of a physical health programme for students, they expressed less agreement about their personal involvement in the programme, as some felt doing so was beyond their call of duty. In Poland, Woynarowska-Soldan (2015) found that school leaders had limited involvement in establishing and managing health-promotion initiatives among school staff.…”
Section: Resultsmentioning
confidence: 99%
“…87 A socialecological perspective was used to investigate the CSPAP involvement of a national sample of principals. 88 Results showed that intrapersonal factors (i.e., beliefs about the outcomes of a CSPAP) directly predicted the principals' CSPAP involvement, while interpersonal (i.e., parents and teachers support of the program) and environmental factors (i.e., support from the school, the community, and public policy) were predictors of intrapersonal factors.…”
Section: Other Physical Activity Opportunitiesmentioning
confidence: 91%
“…35 The support of principals and other school administrators is essential to the success of school-based initiatives. 88 While research on the role of classroom teachers and physical education teachers is important to understanding "bottom up" approaches to CSPAP implementation that rely on the volitional support of school staff who directly interact with children, it is equally important to understand "top down" approaches that capitalize on the decision-making power of higher-level entities in the school system, which can lead to increased accountability for CSPAP implementation.…”
Section: Recommendations For Advancing the Knowledge Basementioning
confidence: 99%
“…These included collaboration (e.g., involvement in planning and programming); advocacy (e.g., policy involvement); and support (e.g., professional development and technical assistance). In addition, researchers (Orendorff et al, 2020) found that intrapersonal variables, such as expected outcomes of a CSPAP, directly predicted school principals' selfreported CSPAP involvement, while interpersonal (e.g., parent and teacher support for CSPAPs) and environmental variables (e.g., overall school, community, and policy support for CSPAPs) indirectly predicted such involvement. These findings highlight not only the importance of administrative support in promoting a CSPAP, but also the importance of strong working relationships among school professionals and also between the school, families, and the local community in bringing a CSPAP to fruition.…”
Section: Physical Education In the Covid Eramentioning
confidence: 99%